Peranan Dinas Perdagangan dan Perindustrian dalam Pengawasan Pasar Talang Banjar di Wilayah Kota Jambi - Nuraini, Nuraini; Ansori, Mhd. (Wajah Hukum, 2023)
This research aims to find out and understand the role of the Department of Trade and Industry in supervising the Talang Banjar Market in the Jambi City area, the obstacles encountered in supervising the Talang Banjar Market in Jambi City, what efforts have been made to overcome these obstacles. This type of research is empirical juridical. The results of the research are the role of the Trade and Industry Service in supervising the Talang Banjar Market in the Jambi City area, namely by arranging street vendors, controlling street vendors, and coaching street vendors. The obstacle encountered in monitoring the Talang Banjar Market in Jambi City was the presence of individuals protecting traders selling on the side of the road. Efforts made to overcome these obstacles are by implementing sanctions against street vendors in the context of organizing and empowering street vendors in Jambi City. So far, the implementation of sanctions has not been optimal. This is because law enforcement officers are not firm in providing sanctions and the level of legal awareness of the community (street vendors) is still not good. This legal awareness is closely related to the formation of a good legal culture.